The initial results of using brolucizumab (Beovu®), an angiogenesis inhibitor, for choroidal neovascularization in patients with age-related macular degeneration - N.S. Zhayvoronok; O.V. Kolenko; L.P. Danilova; E.L. Sorokin (РМЖ "Клиническая офтальмология")
N.S. Zhayvoronok1, O.V. Kolenko1–3, L.P. Danilova1,2, E.L. Sorokin1,3 1Khabarovsk Branch of the S. Fedorov Eye Microsurgery Federal State Institution, Khabarovsk, Russian Federation 2Institute of Advanced Training of Healthcare Specialists, Khabarovsk, Russian Federation 3Far Eastern State Medical University, Khabarovsk, Russian Federation Aim: to assess the clinical efficacy of brolucizumab for choroidal neovascularization (CNV) in patients with age-related macular degeneration (AMD). Patients and Methods: clinical assessment of the efficacy of brolucizumab was performed in 25 patients (25 eyes) with neovascular AMD. The dynamic monitoring included optical coherence tomography to assess the localization and area of the neovascular complex, as well as the density and thickness of the new blood vessels (OCT-angiography). Three injections of brolucizumab (in a dose of 6 mg/0.05 mL) were performed once a month. The follow-up period was 4 months. Results: the mean age of patients was 68±5 years. After the first injection of brolucizumab, there was a statistically significant decrease in the mean values of central retinal thickness (CRT) and macular volume (MV) vs the baseline values. By month 4, a statistically significant increase in the best corrected visual acuity (BCVA) vs. that at the baseline was achieved: from 0.3 (0.2; 0.45) to 0.6 (0.4; 0.6) (p<0,001). In all patients after three injections the minimal values of CRT were reported: they decreased from 298 (284; 302) to 268 (263; 270) µm. Also, MV reduced from 10.4 (9.5; 10.7) to 8.8 (8.7; 9.3) mm3 (p<0,001). After one month in 22 of 25 patients and after three intravitreal injections of brolucizumab in 3 patients an adhesion of the neuro- and pigment epithelium was recorded with the complete resorption of the subretinal fluid, and the subretinal fluid was not found. Subjectively, all patients noted an improvement in the quality and contrast sensitivity of central vision after treatment. Conclusions: after each injection of brolucizumab, there was a statistically significant progressive reduction in macular parameters, CRT and MV, coupled with an increase in mean BCVA values. Keywords: vascular endothelial growth factor, anti-VEGF, brolucizumab, age-related macular degeneration, neovascular age-related macular degeneration, wet age-related macular degeneration, treatment efficacy. For citation: Zhayvoronok N.S., Kolenko O.V., Danilova L.P., Sorokin E.L. The initial results of using brolucizumab (Beovu®), an angiogenesis inhibitor, for choroidal neovascularization in patients with age-related macular degeneration. Russian Journal of Clinical Ophthalmology. 2022;22(4):228–233 (in Russ.). DOI: 10.32364/2311-7729-2022-22-4-228-233.